(untitled) (Polifonia, 1994)
ABSTRACT: This study proposes two possible ways of reading/interpreting the intriguing poem "A casa", by Vinícius de Moraes: One addresses the virtual receiver, the child, in consonance with the children’s imagination, and the other addresses the poet’s own lyric self which did not allow himself to be bounded by any ties.